2010
DOI: 10.1177/0040517510371863
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Staple Strength and Raw Wool Blend Make-Up on Processing and Properties from Top to Fabric

Abstract: The impact of staple strength on later stage processing of fine fleece wools (19 µm) and the blending with pieces is investigated. The staple strength findings complement those of previous researchers who used wools of different fibre diameters or from single flocks. The results reported here show that, as previously, the direct effect of staple strength is limited to the production of tops, where staple strength influences fibre length in the top and the generation of combing waste. Blending fleece wool and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Thus, although staple strength for the three batches has influenced topmaking performance, and Hauteur as shown in Figure 5, the strength ratios suggest staple strength has little bearing on bundle tenacity and therefore spinning performance and yarn quality as described below. Yu et al [16] conducted bundle tenacity tests on 66 wool tops before and after dyeing with different dyes and colors. Their experimental results showed that the dyeing damage measured in terms of a reduction in the fiber bundle strength was of the order of 6-7% on average, while some tops exhibited reductions as high as 14%.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, although staple strength for the three batches has influenced topmaking performance, and Hauteur as shown in Figure 5, the strength ratios suggest staple strength has little bearing on bundle tenacity and therefore spinning performance and yarn quality as described below. Yu et al [16] conducted bundle tenacity tests on 66 wool tops before and after dyeing with different dyes and colors. Their experimental results showed that the dyeing damage measured in terms of a reduction in the fiber bundle strength was of the order of 6-7% on average, while some tops exhibited reductions as high as 14%.…”
Section: Resultsmentioning
confidence: 99%